SCIENCE-EDUCATION-PRODUCTION INTEGRATION - Egamberdiyev Shavkatbek; Adxamov Asadbek (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article reflects on the prospects at the end of the process of troubleshooting and integrating the problems encountered in the integration of Science-Education-production. Information is provided on the work carried out on the integration of Science and education and production